Portable Wind Turbine for Energy Recharging Device Applications - Joni Welman Simatupang; Kristiantho Sulistiohadi (President University, 2016)
A new design of a portable, inexpensive, and easy to assemble horizontal axis wind turbine (HAWT) system for harnessing wind energy that can be reproduced by individuals in the need of electricity has been implemented. The design still follows the Betz’ law theory to define the maximum electrical power that can be extracted from the wind in an open flow area. From our measurement data, the Betz Limit (C) of our design wind turbine is approximately 0.48, meaning it can capture not more than 48% of the incoming kinetic energy of the wind. It was found also that the system can generate a stable at least 5V and 1A of DC voltage and current, respectively. The wind speed is at least ranging from 35 to 55 km/h (∼10 to 15 m/s). We conclude that this HAWT is still able to charge some rechargeable energy recharging devices, such as smart phone or power bank. This HAWT must be put outside to obtain a good amount of wind. But, actually it does not provide a waterproof protection system to make it usable in a rainy season. For further research, a new portable wind turbine can be designed to generate more electric power with waterproof ability system such like using PVC or acrylic which is modeled by this simple prototype.Keywords: Betz Limit, energy recharging devices, harness, maximum power, portable.